Exergy analysis of laminar forced convection of nanofluids through a helical coiled tube with uniform wall heat flux. (9th August 2013) - Ahadi, M.; Abbassi, A.
In this paper, entropy generation in nanofluids has been studied analytically. For this purpose, the fully developed laminar forced convection of Al2 O3 –water nanofluid through helical coiled tubes is investigated. The nanofluid has been considered to be a single–phase homogeneous fluid. Entropy generation rates due to heat transfer and friction loss, and the total entropy generation rate have been derived for nanofluids, and the effects of various coil and flow parameters on the entropy generation rates have been analysed. The results showed that increasing the basefluid's Reynolds number, nanoparticles concentration, and curvature ratio causes thermal entropy generation to decrease and frictional entropy generation to increase. Further, the variation of the dimensionless pitch has a minor effect on the total entropy generation distribution of nanofluids, and can be set to a constant value, whereas the effects of the nanoparticles concentration on the total entropy generation rate are major, and cannot be neglected.